A Survey of Wireless Communication Technologies in Internet of Things - Avatade, M; Lal, M; Jain, A (International Journal of Computer Sciences and Engineering, 2025)
The main Motive of Internet of Things is to segregate everything in our world under a common controlled environment that will give us control of day to day life things, as well as providing us status updates of the things. In Accordance with this, Effective implementation of Internet of Things is completely depends upon Technologies and protocols incorporated to communicate between electronic devices and its controlling circuitry. This paper Introduces about basic standards and parameters of the various Communication technologies inculcated in Internet of Things. In this paper, we illustrated the survey of key technologies involved in the implementation of Internet of Things along with the wide application area where the Internet of Things will have major role. We also discussed about detailed comparison of different parameters of various wireless Communication technologies